Effects of heat strain on cognitive function among a sample of miners. (July 2022) - Yeoman, Kristin; Weakley, Alyssa; DuBose, Weston; Honn, Kimberly; McMurry, Timothy; Eiter, Brianna; Baker, Brent; Poplin, Gerald
Abstract: Heat stress is associated with workplace injuries, likely through a combination of fatigue, reduced cognitive function, and thermal discomfort. The purpose of this study was to evaluate four cognitive tasks for sensitivity to heat stress. Eight participants performed treadmill exercise followed by assessments of serial reaction time (RT), Stroop effect, verbal delayed memory, and continuous performance working memory in an environmental chamber. A control (21.1 °C) trial, and "Hot 1" and "Hot 2" (both 37.8 °C) trials were run sequentially on two separate days to evaluate the four cognitive tasks. Heat strain (comparing Hot 1 and Hot 2 with the control trial) resulted in impairments in the serial RT test response and Stroop accuracy. Delayed memory was impacted only in the Hot 2 trial compared with the control trial. Given the demonstrated impact of heat on cognitive processes relevant to workers' real-world functioning in the workplace, understanding how to assess and monitor vigilant attention in the workplace is essential. Highlights: We evaluated four cognitive tasks for sensitivity to heat stress and feasibility of field-based measurement. Heat stress impacted vigilant attention, inhibition of automatic responses, and verbal memory, but not working memory. The serial reaction time task measuring vigilant attention was sensitive to heat stress and feasible for field-based use. Heat stress had a greater effect on serial reaction time than Stroop, Hopkins Verbal Learning Test-Revised, and N-back tests. Delayed stimulus responses during the second of two trials in a hot chamber suggest a cumulative effect of heat on vigilance.